Younger children more likely to be diagnosed with ADHD not necessarily due to bias. Issue 12 (13th November 2020) - Knopf, Alison
Abstract : A study published in the October issue of Pediatrics by Vuori et al. found that the youngest children in the classroom are at the highest risk of being diagnosed with attention‐deficit/hyperactivity disorder (ADHD), and also at the highest risk of being prescribed medications, compared to older classmates. The study relied on a national registry from Finland and builds on other studies showing that a younger relative age increases the risk of being diagnosed with ADHD.